Emotional and Social Barriers to Engaging in Misinformation Correction on Social Media: A Qualitative Study (American Journal of Arts and Human Science, 2025)
Public discourse, civic trust, and digital well-being are all seriously threatened by the ongoing dissemination of false information on social media. Although platforms and fact-checkers make an effort to prevent false information, user-generated content frequently outpaces these efforts in terms of speed and reach. Although most users rarely step in to correct misinformation within their networks, recent research shows how important it is for regular users to do so. This qualitative study investigates the social and emotional obstacles that prevent people from correcting false information on social media and examines factors that could encourage such corrective action. Twenty-four active social media users from a variety of platforms, ages, and backgrounds participated in semi-structured interviews. With the aid of NVivo software, thematic analysis identified three major themes: (1) emotional costs, including anxiety, emotional exhaustion, and fear of confrontation; (2) social barriers, including worries about destroying relationships; (3) the need for social acceptance; and (4) group norms that discourage dissent and the desire for social acceptance. Even among people with high levels of motivation or digital literacy, the interaction between relational risk and emotional vulnerability produces a vicious cycle that discourages corrective behaviour. The results highlight the need for interventions that use platform design, public education, and theory development to address not only informational but also relational and emotional aspects. Stakeholders can better enable users to contribute to more accurate and healthy digital communication ecosystems by addressing these interconnected barriers.